Effects of Fire and Cutting on Vegetation Physical Properties and Herbivorous Foraging Behavior in the Grassland of Bardia National Park, Nepal - Bhusal, Namrata; Bhusal, Binit; Pokharel, Basudev (Journal of Forest and Natural Resource Management, 2024)
Grasslands are critical ecosystems providing habitats and resources for wildlife. This study investigates the effects of grassland management practices, burning and cutting, on grass species composition and physical properties i.e., height and biomass in burned and cut grassland patches in the Bardia National Park (BNP). The study was carried out at Bagaura Phata of BNP. Vegetation assessment was carried out using point intercept method, with 1m2 quadrant and vegetation samples were hand separated into different parts (green leaf, green stem, dry leaf and dry stem) to compare the physical properties between burnt and cut plots. Likewise, grazing intensity and pattern was quantified by visual inspection of grazing, pellet group count and direct observation. Species diversity index for herbivores was estimated using Shannon’s diversity index. Our findings indicate significant differences in vegetation height between fire-treated and cutting-treated plots. Fire treatment significantly increased grass height, with a mean height of approximately 27.35 cm compared to 23.03 cm in cutting-treated plots. However, no significant disparities were observed in aboveground biomass between the two treatments. Additionally, distinct significant differences were found in the proportion of green leaf and dry leaf between fire-treated and cutting-treated plots, with the proportion of dry leaf being notably lower in fire-treated plots. Correlation analysis showed a negative relationship between grass height and grazing intensity, and between grass height and pellet group counts in both treatment types, indicating that grazing intensity decreases as vegetation height increases. No significant disparities were observed in grazing intensity between cutting and fire treatments. BNP contains more than 60 grass species of different families. There was no difference in the presence of individual grass species but difference between the plots receiving cutting and fire as a treatment- high presence of forbs species in the fire treatment. Desmostachya bipinnata, Narega prophyrocoma and Imperata cylindrica were dominant species in fire treatment plots whereas Vetivera zizanoides was dominant in cutting treatment plots. The study recommend for operations that a combination of burning and cutting to maintain biodiversity and optimize habitat conditions for various herbivores.